Analisis Faktor – Faktor yang Berpengaruh terhadap Capaian Nilai Kinerja Pelaksanaan Anggaran pada Kantor Badan Narkotika Nasional Provinsi DIY - Edi Mujayadi; Aftoni Susanto; Salamatun Asakdiyah (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The Ministry of Finance, as the State Treasurer, uses the Budget Implementation Performance Indicators (IKPA) to assess the effectiveness and quality of budget execution within government institutions. However, the fluctuating IKPA scores of the National Narcotics Agency of the Special Region of Yogyakarta (BNNP DIY) over the past five years indicate inconsistencies in planning, human resource competence, regulatory compliance, and coordination. This study aims to analyze how these factors influence the achievement of IKPA performance scores at BNNP DIY. Using a qualitative approach through literature review and in-depth interviews with the finance and budget team, this research explores managerial and operational dynamics that affect budget performance. The findings show that accurate planning, competent human resources, regulatory adherence, and effective inter-unit coordination have a positive and significant influence on improving the IKPA score. These results imply that strengthening managerial capacity and internal coordination can enhance institutional accountability and the quality of budget implementation.